Papillary Thyroid Carcinoma Arising in Thyroglossal Cyst: A Report of Two Cases - Tyagi, Niketa; Gathwal, Monika B; Singh, Kulwant; Gathwal, Chiranjeev; Agarwal, Ruchi; Kaur, Sawaran (Annals of Pathology and Laboratory Medicine, 2025)
Papillary carcinoma arising in a thyroglossal duct cyst is a rare entity, accounting for approximately 1% of all thyroglossal cyst cases. Clinically, it often mimics a benign cystic lesion, making preoperative diagnosis difficult. In most instances, the malignancy is discovered incidentally during histopathological evaluation following surgical excision. We report two cases of papillary carcinoma arising in thyroglossal duct cysts in female patients aged 38 and 37 years, respectively. In both cases, the carcinoma was identified only after routine surgical excision performed for clinically benign-appearing cysts. Histopathological examination revealed features characteristic of papillary thyroid carcinoma originating within the thyroglossal duct cyst. These cases highlight the importance of thorough preoperative evaluation, including high-resolution ultrasound, to assess for solid components, calcifications, or other suspicious features. Furthermore, extensive histological sampling of excised thyroglossal duct cysts-particularly those with solid areas is essential to exclude the presence of malignancy.